2014
DOI: 10.5812/pedinfect.18909
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance by the Health Care Staff in a Pediatric Hospital

Abstract: Background: Hospital acquired infections lead to significant morbidity and mortality in hospitalized patients. Proper implementation of hand hygiene by health care personnel (HCP) prevents nosocomial infections. Objectives: To monitor hand hygiene compliance by the medical and nursing staff in different wards of a children's hospital. Patients and Methods: Four wards were selected for surveillance. In observation periods of 20 minutes each, a trained Pediatric resident observed four patient beds and hand hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Contrary to other studies, after intervention, HH compliance of nurses (72.6%), auxiliaries (65.15%), and medical doctors (82.35%) rose dramatically [1, 5, 6, 9, 12, 15, 3234]. This finding of the present study could be probably due to the small number of observed opportunities among medical doctors or their better recall of previous knowledge after educational intervention.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to other studies, after intervention, HH compliance of nurses (72.6%), auxiliaries (65.15%), and medical doctors (82.35%) rose dramatically [1, 5, 6, 9, 12, 15, 3234]. This finding of the present study could be probably due to the small number of observed opportunities among medical doctors or their better recall of previous knowledge after educational intervention.…”
Section: Discussioncontrasting
confidence: 99%
“…Healthcare-associated infection (HCAI) is one of the most important challenges of healthcare systems due to its strong impact on patient's safety and high financial burden [14]. In developed countries, the prevalence of HCAI is estimated between 5.1% and 11.6% [5].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the ICU staff and environment in HAIs should be considered when devising strategies to prevent or reduce the occurrence of these infections among the highly sensitive patients. There are some reports that showed poor hand hygiene compliance among different hospital staff in Iran [7][8][9]. However, few data exist on the microbial contamination of HCWs' hands and the hospital environment in the studied hospitals.…”
Section: Introductionmentioning
confidence: 85%
“…Generally, researchers acknowledge that improving compliance to HH is a complex issue; despite the fact that most HCPs possess the required knowledge and a positive attitude, compliance with standard HH protocols remains low in most countries (6,9,11,14,15). A study in France noted that continuous education, poster reminders, and compliance by a senior health care worker who served as a role model had a positive effect on overall adherence to HH by the nursing staff (16).…”
Section: Discussionmentioning
confidence: 99%